Elevated plasma prostaglandin E2 levels found in 14 patients undergoing autologous bone marrow or stem cell transplantation. - Cayeux, S; Beverley, P; Schulz, R; Dörken, B (1993)
In the present study, plasma prostaglandin E2 (PGE2) levels were quantitated serially in 14 patients during the period preceding and following autologous bone marrow transplantation (ABMT) or autologous stem cell transplantation (ABSCT). In eight ABMT recipients, the pre-transplant conditioning regimen consisted of combined supralethal doses of chemo- and radiotherapy which was followed by ABMT using autografts purged in vitro either with mafosfamide or monoclonal antibodies (moAbs) plus immunomagnetic beads (IB). A further two ABMT recipients received only high-dose chemotherapy without irradiation as conditioning, followed by unpurged autologous BM. The four ABSCT recipients were also treated solely with chemotherapy followed by untreated autologous stem cell reinfusion. Elevation of plasma PGE2 levels occurred in all 14 patients, despite the difference in the pre-transplant conditioning. The peak levels of PGE2 ranged from about three times the mean value obtained with ten control individuals (29.8 +/- 3.7 pg/ml) to ten times this level. In all cases plasma PGE2 normalised with recovery of the peripheral leucocyte count.